Evaluating the impact of mindfulness-based interventions (MBI) on nurses’ work-related stress levels - Yuseran, Yuseran; Nugraha, Ary; Negara, Candra Kusuma (Science Midwifery, 2025)
Prolonged work stress can disrupt mental health and reduce employee performance, especially nurses who face emotional and physical stress simultaneously. Mindfulness-Based Intervention (MBI) emphasizes full awareness of current experiences as an emotion regulation strategy. This study aims to evaluate the effectiveness of mindfulness-based interventions in reducing work stress levels in nurses. The method of this study was a quasi-experimental study with a one-group pre-post test with 60 nurse respondents selected through purposive sampling. The intervention group was given four weeks of MBI training with mindful breathing, body scan, and self-reflection training sessions, while the control group was not given any intervention. Stress levels were measured using the Perceived Stress Scale (PSS). The Wilcoxon Signed Rank Test and the Mann-Whitney U Test used for analysis. The results showed a significant increase in all aspects of QoL in the intervention group. The average total QoL score increased (p= 0.001) including in satisfaction with therapy (p= 0.001), impact on life (p= 0.002), fear of complications (p= 0.000), and social problems (p= 0.001). No significant changes were found in the control group.